(untitled) (Vietnam Journal of Community Medicine, 2026)
of Pseudomonas aeruginosa isolates collected from inpatients at Nguyen Tri Phuong Hospital during 2024-2025. Methods: 88 non-duplicate isolates underwent antimicrobial susceptibility testing (CLSI 2025), Colistin MIC determination by E-test, and multiplex real‑time PCR screening for blaNDM, blaIMP, blaVIM, blaKPC and mcr-1-mcr-10 genes. Results: Resistance to Imipenem and Meropenem ranged from 42-46%, whereas all isolates remained susceptible to Colistin. Among 32 carbapenemase‑producing isolates, blaNDM predominated (over 50%), surpassing blaIMP (28-29%), with a strong correlation between blaNDM/blaIMP carriage and Carbapenem-resistant phenotypes (p < 0.00001). No mcr variants were detected. Conclusion: The predominance of blaNDM within the P.aeruginosa carbapenemase spectrum, alongside preserved Colistin susceptibility, underscores the importance of molecular surveillance to optimize therapy and strengthen antimicrobial stewardship in hospital settings.